ʻAnus̨ōn ngān phrarātchathān phl̄œng sop Phrakhrū Pathumsiritham (Lek Thammachinō), ʻadit čhaoʻāwāt Wat Bāng D̄ư na mēru l̨ōi Wat Bāng D̄ư ʻAmph̄œ M̄ưang Čhangwat Pathum Thānī, Wan ʻāthit thī 4 Mēsāyon Ph̨ō.S̨ō. 2542 (s.n., 1999)
Cremation volume for Phrakhru Pathumsiritham, the abbot of Wat Bang Du.